Mitochondrial DNA-based identification of developmental stages and empty puparia of forensically important flies (Diptera) in Egypt - Hedayat A Abdel Ghaffar; Marie Z Moftah; Alexandre Favereaux; Mohamed Swidan; Omar Shalaby; Sara El Ramah; Reda Gamal (Wolters Kluwer Medknow Publications, 2018)
Relying on morphology in the estimation of postmortem intervals is not always accurate for all life phases of flies, especially for immature stages. The present study demonstrates the application of cytochrome oxidase I sequences, a partial mitochondrial (mt) gene region, to differentiate forensically important flies in Alexandria, Egypt. Thirty-three adult flies, larvae, and pupae were collected from rabbit carcasses. Nineteen were used for genotyping. Sequence analysis revealed no significant intraspecific divergence in Diptera species. Accordingly, a neighbor-joining tree using the Kimura 2-parameter model illustrated reciprocal morphology between species. Specimens represented five species, four genera, four subfamilies, two families, and one order. We herein identify five different Diptera species, Chrysomya albiceps, Chrysomya megacephala, Calliphora vicina, Lucilia sericata, and Ophyra capensis, using mt DNA as a species-specific marker for identification in a local database set-up.